Web application for Office of International Programs. - Jarugu, Swathi (Kansas State University, 2011)
The mission of the Office of International Programs is to lead the internationalization of Kansas State University by supporting and collaborating with faculty, students, and scholars. The units within the Office of International Programs provide primary support for both in coming international students, faculty and researchers at K-State, faculty and researchers going abroad, etc. It seldom happens that all the international activity of a particular university is organized under the same hood. There is no conventional source that handles all the information (International activity) in a single web application, it is usually scattered over the web. This makes it tough for prospective students or researchers to search for people or programs. Therefore, to overcome this issue, the current project has been implemented. The main objective of the current project is to design a website for the Office of International Programs. This website hosts information about International Faculty, Study Abroad Programs, International Agreements, Alumni Groups and International Students on a single platform. This portal would offer the administrators with different modules where information about a particular program can be added, edited, deleted and viewed. Primary focus of this application is to display information in an innovative format and to enable different users to navigate over the web site easily. This website makes the searching process easy for users. This site is significantly responsible for viewing of information and maintaining a database for various people and programs for Office of International Programs at Kansas State University.
Keywords: Web application; International programs; Computer Science (0984)